The complete mitochondrial genome of the green alga Chloroidium sp. UTEX 3077 (Watanabea clade, Trebouxiophyceae). Issue 1 (2nd January 2020) - Zhang, Huanjun; Zhou, Quanli; Liu, Yuanjin; Chen, Wei; Sun, Wei; Wang, Haiyan; Wang, Zhongquan
Abstract: The complete mitochondrial genome of Chloroidium sp. UTEX 3077 was determined in this study. The circular genome was 90, 774 bp in length with the GC content of 38.8%. It contained 30 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes and 2 ribosome RNA (rRNA) genes. A phylogenetic analysis based on the 8 mitochondrial genomes of Trebouxiophyceae indicated that Chloroidium sp. UTEX 3077 grouped with Chlorellales.